2006
DOI: 10.1021/bm060346n
|View full text |Cite
|
Sign up to set email alerts
|

Electrohydrodynamic Properties of Succinoglycan as Probed by Fluorescence Correlation Spectroscopy, Potentiometric Titration and Capillary Electrophoresis

Abstract: The electrostatic, hydrodynamic and conformational properties of aqueous solutions of succinoglycan have been analyzed by fluorescence correlation spectroscopy (FCS), proton titration, and capillary electrophoresis (CE) over a large range of pH values and electrolyte (NaCl) concentrations. Using the theoretical formalism developed previously for the electrokinetic properties of soft, permeable particles, a quantitative analysis for the electrohydrodynamics of succinoglycan is performed by taking into account, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 40 publications
5
36
1
Order By: Relevance
“…Figure A shows that the present numerical solutions are in very good agreement with the experimental results of Duval et al. .…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Figure A shows that the present numerical solutions are in very good agreement with the experimental results of Duval et al. .…”
Section: Resultssupporting
confidence: 87%
“…(A) Comparison of our computed electrophoretic mobility for ε r = 1 with the experimental results of Duval et al. as a function of salt NaCl concentration, radius of the PE a = 10.8 nm, pH = 10.3, p K A = 4.58, p K B = 8.6, N A = 213 mM, N B = 26 mM, ℓ = 0.635 nm, and E 0 = 10 4 V/m. Variation of mobility with C KCl for (B) N A = N B = 100 mM and (C) N A = N B = 900 mM for different ε r ( = 0.5, 0.75, 1) and different pH ( = 3, 5, 8, 10) when p K A = 2.5, p K B = 9.5, and β = 2.…”
Section: Resultsmentioning
confidence: 99%
“…(1)-(7) disregard (i) polarization of electric double layer by the applied field and (ii) the possible heterogeneity in soft material density distribution within the permeable part of the bacteria, heterogeneity occasioned by possible swelling of the soft bacterial component under low ionic-strength conditions. As extensively demonstrated in previous work [33,36,37], phenomena (i) and (ii) effectively lead to reduced mobility (in magnitude) as compared to those obtained from Eqs. (1)- (7).…”
Section: Volume Charge Density ( 0 ) and Softness Parameter ( 0 ) Of supporting
confidence: 64%
“…In case of bacteria, the soft component is identified as the cell wall and/or possible surface structures like lipopolysaccharides, fimbriae or pili that may extend in aqueous media from few nms up to tenths of microns from the anchoring membrane [34]. The very presence of such components that are permeable to electroosmotic flow while bacteria migrate under action of applied field (electrophoresis), leads to electrokinetic response that substantially differs from that expected on the basis of formalisms valid for conventional hard impermeable particles [34][35][36]. This response is further reflecting the electrostatic and permeability features of the bacteria, both being intrinsically related to the nature, chemical composition and compactness of the soft bacterial component.…”
Section: Evaluation Of Electrohydrodynamic Properties Of L Pneumophimentioning
confidence: 99%
“…Comparable diffusion coefficients have also been determined on isolated succinoglycan, a polysaccharide produced by bacteria (Duval et al 2006). These types of gelforming plankton exudates represent a major component of the colloidal organic matter in the ocean (Aluwihare et al 1997), and have previously been shown to occur in large amounts in the surface water of the Gullmarsfjord, where they are important for the scavenging of organic carbon through their formation of TEP (Waite et al 2005).…”
Section: Discussionmentioning
confidence: 99%